Quality changes in smoked Colisa fasciata from the markets of Manipur during storage - M., Karthikeyan; B., Dhar; B., Kakati; A., Hassan; S., Das (Fishery Technology, 2025)
The traditional smoking process adopted in the state of Manipur, is different from the smoking process adopted else where in the world. Fishes are not salted during the entire smoking process. Smoked fish Colisa fasciata obtained from the market were packed in low density polyethylene pouches (200 gauge thick) and evaluated for its quality during storage. The product had a moisture content of 9.77 %, which showed an increase (p